The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1136/bmj.323.7315.715
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of specialist nurse intervention in heart failure

Abstract: Objectives To determine whether specialist nurse intervention improves outcome in patients with chronic heart failure. Design Randomised controlled trial. Setting Acute medical admissions unit in a teaching hospital. Participants 165 patients admitted with heart failure due to left ventricular systolic dysfunction. The intervention started before discharge and continued thereafter with home visits for up to 1 year. Main outcome measures Time to first event analysis of death from all causes or readmission to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
389
2
19

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(425 citation statements)
references
References 10 publications
(18 reference statements)
15
389
2
19
Order By: Relevance
“…Many of the programs which have shown improvements in patient outcomes have required substantial investments in multi-disciplinary staff time which may prove to be unsustainable and infeasible in practices withlimited resources (Naylor, Brooten, & Jones, 1994;Rich, Beckham, & Wittenberg, 1995;Foranow et al, 1997;Hunt et al, 2002). Newer, less cumbersome programs involving nurse or pharmacist management have shown decreases in hospitalizations and improved quality of life (Blue et al, 2001;Krumholz et al, 2002;Varma, McElnay, Hughes, Passmore, & Varma, 1999;West et al, 1997), but withthe exception of one study (Stewart & Horowitz, 2002), there has been no clear improvement in survival. The modest success of interventions points to the need for a fundamental reexamination of how CHF patients understand and manage their physical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the programs which have shown improvements in patient outcomes have required substantial investments in multi-disciplinary staff time which may prove to be unsustainable and infeasible in practices withlimited resources (Naylor, Brooten, & Jones, 1994;Rich, Beckham, & Wittenberg, 1995;Foranow et al, 1997;Hunt et al, 2002). Newer, less cumbersome programs involving nurse or pharmacist management have shown decreases in hospitalizations and improved quality of life (Blue et al, 2001;Krumholz et al, 2002;Varma, McElnay, Hughes, Passmore, & Varma, 1999;West et al, 1997), but withthe exception of one study (Stewart & Horowitz, 2002), there has been no clear improvement in survival. The modest success of interventions points to the need for a fundamental reexamination of how CHF patients understand and manage their physical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In seven studies, a reduction in the readmission rate, irrespective of cause [1,2,[7][8][9]11,13] was observed, and a reduction of readmissions for heart failure was demonstrated in five studies [1,4,6,11,12]. A statistically significant decrease in the number of days spent in hospital was reported in five studies [1,4,7,8,14].…”
Section: Randomised Studies Of Heart Failure Management Programmesmentioning
confidence: 90%
“…Five studies showed a statistically significant reduction in the combined endpoint of readmissions and/or mortality, irrespective of the reason [5,[7][8][9]14], and two studies reported a statistically significant reduction in the combined endpoint of readmission rates for heart failure and/or death [11,12].…”
Section: Randomised Studies Of Heart Failure Management Programmesmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, nurses are the health professionals most closely involved, according to the meta‐review of 15 meta‐analyses by Savard et al 9 A considerable number of these meta‐analyses mentioned dose titration by HF nurses. In the clinical trials included, nurses titrated ACEIs, ARBs, BBs, K, diuretics, MRAs, and digoxin,10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 assessed the dose reached,13, 14, 19, 20 and initiated treatment following a protocol 10, 12, 14, 15, 17. Hardly any similar research has been conducted in Spain.…”
Section: Introductionmentioning
confidence: 99%